2018
DOI: 10.1093/cje/bey040
|View full text |Cite
|
Sign up to set email alerts
|

Do not take peace for granted: Adam Smith’s warning on the relation between commerce and war

Abstract: Is trade a promoter of peace? Adam Smith, one of the earliest defenders of trade, worries that commerce may instigate some perverse incentives, encouraging wars. The wealth that commerce generates decreases the relative cost of wars; it increases the ability to finance wars through debts, which decreases their perceived cost; and it increases the willingness of commercial interests to use wars to extend their markets, increasing the number and prolonging the length of wars. Smith therefore cannot assume that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…This supports the argument of the school of thought that says nations/communities that trade with each other find conflicts and hostilities between each other unattractive and costly, thereby reducing the probabilities of engaging each other in violent conflict. This finding is also consistent with the empirical findings of Martin et al (2012), Seitz et al (2015), Polachek (1980), Chang et al (2004), Krpec and Hodulak (2019), Paganelli and Schumacher (2019), and Garfinkel and Syropoulos (2015). They found that countries with greater trade engage in the least amount of hostilities.…”
Section: Trade and Internal Conflict In Nigeriasupporting
confidence: 91%
See 1 more Smart Citation
“…This supports the argument of the school of thought that says nations/communities that trade with each other find conflicts and hostilities between each other unattractive and costly, thereby reducing the probabilities of engaging each other in violent conflict. This finding is also consistent with the empirical findings of Martin et al (2012), Seitz et al (2015), Polachek (1980), Chang et al (2004), Krpec and Hodulak (2019), Paganelli and Schumacher (2019), and Garfinkel and Syropoulos (2015). They found that countries with greater trade engage in the least amount of hostilities.…”
Section: Trade and Internal Conflict In Nigeriasupporting
confidence: 91%
“…Other empirical works that have demonstrated a close association between INT-TRAD and INT-CONF include Gasiorowski and Polachek (1982), Fearon (1995), Seitz et al (2015), Paganelli and Schumacher (2019), Chang et al (2004), Garfinkel and Syropoulos (2015), and Martin et al (2012). A few other works examined factors that could influence the relationship between INT-TRAD and INT-CONF.…”
Section: Evidence From the Literaturementioning
confidence: 99%
“…), given the fact that nations were jealous (WN IV.iii.c.9) and would seek to opportunistically take advantage of one another through military force, Smith saw the importance of protecting the sovereignty and security of the nation state, even sometimes at the expense of free trade. Free trade would not necessarily function, in Smith's mind, as a guarantor of peace (Paganelli and Schumacher 2019). It is along such lines that he seems to support the English Navigation Acts, for instance, which were "not 27 Viner (1927, 213) helpfully catalogues four main areas of reform advocated in WN: free choice in occupation, free trade in land, free internal trade, and free trade in commerce "through the abolition of the duties, bounties, and prohibitions of the mercantilistic regime."…”
Section: The Limits Of Focalismmentioning
confidence: 99%
“…He also warned that wealth and trade were good in times of peace but dangerous in times of war (Smith, 1776, p. 494). It is thus fair to say that Smith did not go as far as Montesquieu, Kant, or Mill (see also Paganelli & Schumacher, 2019).…”
Section: Adam Smith Trade and National Defencementioning
confidence: 99%